Secondary Organising Pneumonia Among Immunocompromised Multiple Sclerosis Patients Treated With Ocrelizumab Following COVID‐19 Infection: Two Case Reports With Literature Review - Tarake M. Aljarod; Richard Scott Morehead (Respirology Case Reports, 2025)
ABSTRACT Anti‐CD20 medications, such as rituximab and coronavirus disease 2019 (COVID‐19) infection, have been shown to cause secondary organising pneumonia (OP). Ocrelizumab is an anti‐CD20 monoclonal antibody widely used as a disease‐modifying therapy for relapsing–remitting and primary progressive forms of multiple sclerosis (MS). We describe two cases of biopsy‐proven secondary OP in ocrelizumab‐treated MS patients occurring several weeks after contracting COVID‐19 infection. These cases had been on ocrelizumab for 6.5 years (latent period) before the development of OP. Withdrawal of ocrelizumab and corticosteroids resulted in clinical and radiographic recovery. Literature review revealed seven cases of secondary OP in ocrelizumab‐treated MS patients without evidence of infection and 10 MS cases with secondary OP due to COVID‐19 infection in the setting of ocrelizumab treatment. Although unproven, ocrelizumab could trigger pneumotoxicity in patients when combined with COVID infection.